Niveles de Interleucina y su receptor soluble antes y después de la cirugía y/o transfusión - González, Maczy; Arteaga-Vizcaino, Melvis; Ruiz, Ana; Quintero, Maribel; Villasmil, Jessica; Díaz, Felipe; Osorio, Sergio; Weir, Jesús (Vitae, 2013)
Determinar los niveles de IL-2 y RsIL-2 antes y después de una cirugía y/o transfusión.. 80 pacientes clasificados en 2 grupos de estudio: A: 40 sometidos a cirugía y transfusión y B: 40 a cirugía, se les determinó IL-2 y RsIL-2 antes y 24 horas después de la cirugía, empleando ELISA. Obteniéndose valores promedio: grupo A, IL-2 de 3,98 U/ml antes, 3,18 U/ml bolsa, no detectable después; 678,2 pg/ml, 1402 pg/ml y 90,34 pg/ml RsIL-2 respectivamente. B: 0,938 U/ml y 0,139 U/ml IL-2, 364,8 pg/ml y 497 pg/ml RsIL-2 en cirugía menor; 2,03 U/ml y 0,114 U/ml IL-2; 319,7 pg/ml y 600 pg/ml RsIL-2 en cirugía mayor respectivamente. De estos resultados se puede inferir que pareció ocurrir un declive de la función linfocitaria después de una cirugía y/o transfusión, atribuible a una posible alteración de la respuesta inmunitaria celular, que aunado a la alteración Title Seric levels of interleukin-2 and its soluble receptor Abstract This study was designed to determine interleukin-2 (IL-2) levels and sIL-2R levels before and after surgery and/or blood transfusion. Two groups of study (80 patients) were classified as: A: (n=40) which were subjected to surgery and blood transfusion and B: on which only surgery was performed. IL-2 and sIL-2R was estimated 24 hours before and after surgery employing ELISA. Average values for the group A de IL-2 de 3,98 U/ml before, 3,18 U/ml hemoderivative, undetectable after; 678,2 pg/ml, 1402 pg/ml and 90,34 pg/ml sIL-2R respectively. B: 0,938 U/ml and 0,139 U/ml IL-2, 364,8 pg/ml and 497 pg/ml RsIL-2 in minor surgery; 2,03 U/ml and 0,114 U/ml IL-2; 319,7 pg/ml and 600 pg/ml RsIL-2 in major surgery respectively. The decline in lymphocite function after surgery and/or blood transfusion, is attributed to a defective cell immune response, including cytokines alteractions seemed to contribute to the downregulation of the optimum function of the immune system.